Anticipated Classes of New Medications and Molecular Targets for Pulmonary Arterial Hypertension. (1st January 2013) - Morrell, Nicholas W.; Archer, Stephen L.; DeFelice, Albert; Evans, Steven; Fiszman, Monica; Martin, Thomas; Saulnier, Muriel; Rabinovitch, Marlene; Schermuly, Ralph; Stewart, Duncan; Truebel, Hubert; Walker, Gennyne; et al.
Abstract : Pulmonary arterial hypertension (PAH) remains a life‐limiting condition with a major impact on the ability to lead a normal life. Although existing therapies may improve the outlook in some patients there remains a major unmet need to develop more effective therapies in this condition. There have been significant advances in our understanding of the genetic, cell and molecular basis of PAH over the last few years. This research has identified important new targets that could be explored as potential therapies for PAH. In this review we discuss whether further exploitation of vasoactive agents could bring additional benefits over existing approaches. Approaches to enhance smooth muscle cell apotosis and the potential of receptor tyrosine kinase inhibition are summarised. We evaluate the role of inflammation, epigenetic changes and altered glycolytic metabolism as potential targets for therapy, and whether inherited genetic mutations in PAH have revealed druggable targets. The potential of cell based therapies and gene therapy are also discussed. Potential candidate pathways that could be explored in the context of experimental medicine are identified.